The Effect Of Work Discipline, Competency, And Integrity, On Employee Performance In Regional Secretariat Environment In Pariaman City - Marlinda, Marlinda; Hasan, Helmi (Program Pascasarjana Universitas Negeri Makassar, 2021)
This study aims to determine the following: 1) The effect of work discipline on employee performance in the Regional Secretariat of Kota Pariaman. 2) The influence of competence on employee performance in the Regional Secretariat of Kota Pariaman. 3) The effect of integrity on employee performance in the Regional Secretariat of Kota Pariaman. 4) The effect of work discipline on employee integrity in the Regional Secretariat of Kota Pariaman. The data collection method is a part of the data collection instrument that determines the success or failure of a study. This type of research uses an associative quantitative approach. To get the data needed in this study, the authors used techniques in data collection. The data analysis technique used in this research is quantitative analysis. The types of data collected in this study were taken from two sources, namely primary data and secondary data. Hypothesis testing in this study was carried out by path analysis. Based on the results of analysis and discussion, it is known that 1) Work discipline has an effect on employee performance (Px1y) is 0.232 with a significance value of 0.007. 2) Job competence has a significant effect on employee performance (Px2y) is 0.462 with a significance value of 0.000. 3) Integrity has a significant effect on employee performance (Px3y) is 0.230 with a significance value of 0.009. 4) Work discipline has no significant effect on integrity (Px1x3) is 0.175 with a significance value of 0.096. 5) Competence has a significant effect on integrity (Px2x3) is 0.508 with a significance value of 0.000. Hypothesis testing in this study was carried out by path analysis. Based on the results of analysis and discussion, it is known that 1) Work discipline has an effect on employee performance (Px1y) is 0.232 with a significance value of 0.007. 2) Job competence has a significant effect on employee performance (Px2y) is 0.462 with a significance value of 0.000. 3) Integrity has a significant effect on employee performance (Px3y) is 0.230 with a significance value of 0.009. 4) Work discipline has no significant effect on integrity (Px1x3) is 0.175 with a significance value of 0.096. 5) Competence has a significant effect on integrity (Px2x3) is 0.508 with a significance value of 0.000. Hypothesis testing in this study was carried out by path analysis. Based on the results of analysis and discussion, it is known that 1) Work discipline has an effect on employee performance (Px1y) is 0.232 with a significance value of 0.007. 2) Job competence has a significant effect on employee performance (Px2y) is 0.462 with a significance value of 0.000. 3) Integrity has a significant effect on employee performance (Px3y) is 0.230 with a significance value of 0.009. 4) Work discipline has no significant effect on integrity (Px1x3) is 0.175 with a significance value of 0.096. 5) Competence has a significant effect on integrity (Px2x3) is 0.508 with a significance value of 0.000. it is known that 1) Work discipline has an effect on employee performance (Px1y) is 0.232 with a significance value of 0.007. 2) Job competence has a significant effect on employee performance (Px2y) is 0.462 with a significance value of 0.000. 3) Integrity has a significant effect on employee performance (Px3y) is 0.230 with a significance value of 0.009. 4) Work discipline has no significant effect on integrity (Px1x3) is 0.175 with a significance value of 0.096. 5) Competence has a significant effect on integrity (Px2x3) is 0.508 with a significance value of 0.000. it is known that 1) Work discipline has an effect on employee performance (Px1y) is 0.232 with a significance value of 0.007. 2) Job competence has a significant effect on employee performance (Px2y) is 0.462 with a significance value of 0.000. 3) Integrity has a significant effect on employee performance (Px3y) is 0.230 with a significance value of 0.009. 4) Work discipline has no significant effect on integrity (Px1x3) is 0.175 with a significance value of 0.096. 5) Competence has a significant effect on integrity (Px2x3) is 0.508 with a significance value of 0.000. 230 with a significance value of 0.009. 4) Work discipline has no significant effect on integrity (Px1x3) is 0.175 with a significance value of 0.096. 5) Competence has a significant effect on integrity (Px2x3) is 0.508 with a significance value of 0.000. 230 with a significance value of 0.009. 4) Work discipline has no significant effect on integrity (Px1x3) is 0.175 with a significance value of 0.096. 5) Competence has a significant effect on integrity (Px2x3) is 0.508 with a significance value of 0.000.